2(x-5)+7=-3

Simple and best practice solution for 2(x-5)+7=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-5)+7=-3 equation:


Simplifying
2(x + -5) + 7 = -3

Reorder the terms:
2(-5 + x) + 7 = -3
(-5 * 2 + x * 2) + 7 = -3
(-10 + 2x) + 7 = -3

Reorder the terms:
-10 + 7 + 2x = -3

Combine like terms: -10 + 7 = -3
-3 + 2x = -3

Add '3' to each side of the equation.
-3 + 3 + 2x = -3 + 3

Combine like terms: -3 + 3 = 0
0 + 2x = -3 + 3
2x = -3 + 3

Combine like terms: -3 + 3 = 0
2x = 0

Solving
2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '2'.
x = 0

Simplifying
x = 0

See similar equations:

| 15(x)=36 | | z-0.09=2.22-0.1x | | .5x-3+1=2x-20-3 | | (x-1)(2x-3)=2x-17 | | -90=3x+5x-10 | | f(3)=-3x | | 5x+3(2x-9)=-21 | | y+1=2(x-4) | | Y-4=0.7(x-3.5) | | -6(-2x-2)=108 | | 3s+-5=-11 | | x-4x=6x+18 | | -3x+9=5x-71 | | 3(1+2x)=-6x+87 | | 5x-7=9+1 | | -2x+4x-33=9 | | Y-3.5=0.7(x-4) | | -4x+3=3-6x | | -4X-6Y+2Z=-2 | | n2+5=15 | | f(-1)=-3x | | -4(5m+20)=-400 | | 12-6z=2x+15 | | 7x+19=21 | | 6X+9Y-3Z=3 | | 3(3)(-3)-8(2)-3= | | -z^4+17z^2-16=0 | | 8c-71=12c-72-4c | | 3(-3+2x)=3x+3 | | 7(-2x-4)=-168 | | -(-2)+2(2.1)-(-2)= | | 51x-.83x^2=0 |

Equations solver categories